PENERPAN ALGORITMA BINARY SEARCH DALAM PENCARIAN DATA POTENSI INVESTASI DI KABUPATEN SELUMA DENGAN SMARTPHONE - Onsardi, Onsardi; Muntahanah, Muntahanah; Toyib, Rozali (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
Seluma Regency has several attractive investment sectors to develop, such as coal mining, shrimp ponds, oil palm plantations, weaving and tourism, the Seluma Government has tried to collect this potential data and package it in the form of a regional book and the limited costs do not allow to produce the book en masse so that digitalization of the data is needed but the data is large, difficult to access with keywords. Search Algorithm In general, search is defined as looking for data by tracing where the data is stored, Searching is the process of searching or searching, Binary search is a method of searching data that has been ordered. In this method all ordered data elements will be tested one by one until the desired element is found. Searching for sorted data will result in a fast search. This algorithm is used for fast search times. The test results are the largest potential area in Seluma Regency is the agriculture and animal husbandry sector (fisheries), then followed by mining and tourism sectors. Efficient and faster Binary Search Algorithm if looking for a value in a large amount of data, Because these data have been sorted first first and the complexity of the algorithm is smaller, the first drawback of Binary Search is that data must be sorted first so that the search process can run well and is more complicated.